See think act scale: Validation of the Dutch version of a measure of relational security in high secure forensic psychiatric care - de Vries, Meike G.; Verkes, Robbert-Jan; Bulten, Berend H. (Frontiers in Psychiatry, 2022)
Relational security is considered an essential form of security in forensic psychiatric care. Research on relational security is important, but is hampered by the lack of instruments to assess and monitor this concept in clinical practice. Within this current study the psychometric properties of the Dutch version of the See Think Act (STA) scale, an instrument designed to measure relational security as perceived by forensic staff members within secure settings, was studied. Results show that the internal consistency of the STA total scale was good. However, the internal consistency of the subscales was relatively low compared to other studies using the original English or the Chinese version of the STA scale. The factor structure found in the original English version of the scale was not confirmed within this sample. With regard to the validity of the instrument results were promising, finding relationships with aspects of ward climate and team reflexivity. Further research and development is needed regarding the STA scale, making it more suitable for monitoring and studying this clinically relevant concept in forensic care.